Quantifying and controlling catastrophic risks - Garrick, B. John (Academic Press/Elsevier, 2008)
The perception, assessment and management of risk are increasingly important core principles for determining the development of both policy and strategic responses to civil and environmental catastrophes. Whereas these principles were once confined to some areas of activity i.e. financial and insurance, they are now widely used in civil and environmental engineering. Comprehensive and readable, Civil and Environmental Risk: Mitigation and Control, provides readers with the mathematical tools and quantitative methods for determining the probability of a catastrophic event and mitigating and controlling the aftermath. With this book engineers develop the required skills for accurately assessing risk and formulating appropriate response strategies. The two part treatment starts with a clear and rigorous exposition of the quantitative risk assessment process, followed by self-contained chapters concerning applications. One of the first books to address both natural and human generated disasters, topics include events such as pandemic diseases, climate changes, major hurricanes, super earthquakes, mega tsunamis, volcanic eruptions, industrial accidents and terrorist attacks. Case studies appear at the end of the book allowing engineers to see how these principles are applied to scenarios such as a super hurricane or mega tsunamis, a reactor core melt down in a nuclear plant, a terrorist attack on the national electric grid, and an abrupt climate change brought about by a change in the ocean currents in the North Atlantic. Written by the current Chairman of the U.S. Nuclear Waste Technical Review Board, Environmental risk managers will find this reference a valuable and authoritative guide both in accurately calculating risk and its applications in their work. Key Features Mathematical tools for calculating and Controlling Catastrophic Risk Presents a systematic method for ranking the importance of societal threats Includes both Natural and Industrial Catastrophes Case studies cover such events as pandemic diseases, climate changes, major hurricanes, super earthquakes, mega tsunamis, volcanic eruptions, industrial accidents, and terrorist attacks.